Enhancement of text-based advanced encryption standard algorithm (AES) in the android platform / Mohamad Zakirin Mohammad Zahari - Mohammad Zahari, Mohamad Zakirin (2014)
Cryptography is a one of the method to provide the secrecy of information or data. Nowadays, there are a lot of cryptography method has been applied. One of the most popular cryptography methods is Advance Encryption Standard (AES). On this paper, the research will focus on the AES encryption and decryption computational process of the text in the Android platform. AES algorithm been chosen because it is one of the most secured cryptography methods, very flexible, and most commonly implemented. However, AES users or application that using AES algorithm might face the problem of computational overhead. The enhanced AES-128 bit algorithm was omitted the mix column step from second round until the ninth round and being replaced with shift row step. This will help to speed up the algorithm because mix column step was using high calculation and needs a lot of time to process it. Based on the research that had been conducted, it shows that the enhanced algorithm have managed to speed up the computational process for encryption and decryption of the text in the Android platform to reduce computational overhead. Therefore, hopefully in future, any cryptography developers can implement this code if they want to encrypt the complex data. In future, the test toward the strength of this enhanced AES-\ 28 bit algorithm should be conducted.